A study on the causal relationship between "the flow of a game" and its outcome in basketball: Focusing on the interdependence relations of four periods - Uchiyama, H.; Ikeda, E.; Yoshida, K.; Machida, Y.; Amino, T.; Kashiwakura, H. (International Journal of Sport & Health Science, 2021)
The purpose of this study was to clarify the causal relationship between the "flow of a game" that can be defined "the situation on which 4 periods which consist of division time as 10 minutes are advancing gradually while having an influence each other" and its outcome, focusing on the interdependence relations of four periods in basketball. In order to accomplish this purpose in this study, a hypothesis was set in that, the "flow of a game," in which "factors causing changes in conditions" cannot be overlooked in basketball, consists of four periods, with each first generating functions as opportunity, in the end affecting the outcome. In order to test this hypothesis, an analysis was performed over 1044 periods in 261 games in Japan`s strongest university league, Kanto Men`s First Division League, based on the following three analysis perspectives: (1) the importance of each period; (2) the mutual dependency between periods; and (3) the relationship between the difference in cumulative scoring and outcome. Results observed using logistic regression analysis and structural equation modeling of the obtained data clarified the following three points: (1) periods that exerted influence on the outcome were the first, third and fourth, with their importance ranked as "third > first > fourth > second"; (2) as for mutual dependency for each period, the point difference in the preceding period in the sequence, "first - second (cumulative)," "second (cumulative) - third (cumulative), "third (cumulative) - fourth" creates an opportunity for the following period; and (3) if there is the cumulative score difference within eight points by the end of the third period, there is a high possibility (potential) for coming back to win. These findings will be able to apply to coaching in various games under the official rules of FIBA as new practical guidelines for closely analyzing the causal relationships between the unique "flow of a game" and outcomes in basketball that take place over four periods.